Effectiveness of Nesting and Swaddling Technique on Biophysiological Parameters, Neuro-behavioral Activity, and Sucking Response among Sick Neonates of Selected Pediatrics Units of Navi Mumbai - Ganesh Reddy, Deepa; Solomon, Smriti G. (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: This study examined the effects of Nesting and Swaddling on bio-physiological parameters, neuro-behavioural activity, and sucking reflex in ill neonates. Method: The researcher used a quantitative and quasi-experimental approach in this investigation. The study included sick Neonates in pediatric unit of selected hospitals Navi Mumbai. Sample size for the study is 200. Result: The experimental normal delivery group reported 56% temperatures over 99.3F. The experimental cesarean group had 54% temperatures over 99.3 F. Sick neonates have mean neuro-behavioral activity of 1.88 with SD 0.89 in the experimental normal delivery group and 1.84 with SD 0.86 in the experimental caesarean group. Sucking response of sick neonates shows 44% of experimental normal delivery group has poor feed. About 54% of experimental cesarean patients were inadequately fed. About 70% of experimental normal delivery group had 97.5–99.3 F. After Nesting and Swaddling, 60% of experimental caesarean delivery patients had 97.5–99.3 F. After nesting and swaddling, sick babies’ neuro-behavioural activity is 2.96 with SD 1.45 in the experimental normal birth group and 3.5 with SD 1.16 in the experimental cesarean group. After nesting and swaddling, 68% of experimental normal birth group sick babies had reasonably effective feed by post-test sucking. At least 50% of experimental cesarean birth patients had effective feed. Conclusion: This study shows that nesting and swaddling sick neonates improves biophysiological measures, neuro-behavioural activity, and sucking reflex. Sick newborns’ biophysiological measurements, neuro-behavioural activity, and sucking response score improve.